ANALISIS PERILAKU PELANGGAN GENERASI Y DAN Z DALAM MEMILIH COFFEE SHOP BRAND LOKAL - Tria Husnul Chotimah; Asep Parantika (LPSDI Bina Patria, 2022)
Currently coffee is increasing every year, coffee lovers today are not only parents but nowadays coffee is also favored by generations y and z. Coffee shops today have grown rapidly and coffee shops today can be found in malls, outlets and offices. Currently, local brands attract attention for young people because they have facilities such as wifi, air conditioning, power plugs, toilets, private rooms and musholahs and Instagramble photo spots. Based on this background, it aims to find out the factors for choosing local brand coffee and find out the activities carried out by generations y and z in the coffee shop.This research uses descriptive qualitative and to collect data through interviews, observations and literature studies, in this study was conducted with 10 visitors, 1 owner and 1 barista which was carried out at the coffee shop Salihara patro 24a and Salihara hangout. The results of the research genarisi y and z like local brands because, the menu varies, the price is relatively a place where the atmosphere is comfortable and easy to go to and the facilities in the coffee shop and close to campus. Their usual activities during the coffee shop are hanging out and chatting, doing tasks, exchanging ideas and enjoying coffee and other activities in the coffee shop